Rational Design of Disulfide Bonds Increases Thermostability of a Mesophilic 1,3-1,4-β-Glucanase from Bacillus terquilensis. - Chengtuo Niu; Linjiang Zhu; Xin Xu; Qi Li (PLoS ONE, 2016)
1,3-1,4-β-glucanase is an important biocatalyst in brewing industry and animal feed industry, while its low thermostability often reduces its application performance. In this study, the thermostability of a mesophilic β-glucanase from Bacillus terquilensis was enhanced by rational design and engineering of disulfide bonds in the protein structure. Protein spatial configuration was analyzed to pre-exclude the residues pairs which negatively conflicted with the protein structure and ensure the contact of catalytic center. The changes in protein overall and local flexibility among the wild-type enzyme and the designated mutants were predicted to select the potential disulfide bonds for enhancement of thermostability. Two residue pairs (N31C-T187C and P102C-N125C) were chosen as engineering targets and both of them were proved to significantly enhance the protein thermostability. After combinational mutagenesis, the double mutant N31C-T187C/P102C-N125C showed a 48.3% increase in half-life value at 60°C and a 4.1°C rise in melting temperature (Tm) compared to wild-type enzyme. The catalytic property of N31C-T187C/P102C-N125C mutant was similar to that of wild-type enzyme. Interestingly, the optimal pH of double mutant was shifted from pH6.5 to pH6.0, which could also increase its industrial application. By comparison with mutants with single-Cys substitutions, the introduction of disulfide bonds and the induced new hydrogen bonds were proved to result in both local and overall rigidification and should be responsible for the improved thermostability. Therefore, the introduction of disulfide bonds for thermostability improvement could be rationally and highly-effectively designed by combination with spatial configuration analysis and molecular dynamics simulation.